Clinical Challenges in Primary Erythromelalgia: A Real-Life Experience from a Single Center and a Diagnostic-Therapeutic Flow-Chart Proposal - Andrea Michelerio; Carlo Tomasini; Eloisa Arbustini; Camilla Vassallo (Dermatology Practical & Conceptual, 2023)
Introduction: Primary erythromelalgia (EM) is a rare clinical syndrome characterized by recurrent erythema, burning pain and warmth of the extremities. The symptoms greatly compromise the patients' quality of life leading to severe disability. SCN9A mutations can be the cause of the disease. Dermatologists are often the specialists these patients turn to for assistance.